Risk Analysis of Port Facility Security Based on the International Ship and Port Facility Security Code (ISPS CODE) - Mohammad Danil Arifin (International Journal of Marine Engineering Innovation and Research, 2024)
The ISPS Code was created in response to the terrorism that occurred on September 11, 2001, in the United States. This prompted the IMO to review and draft the ISPS Code, which was then agreed to be included in the amendments to SOLAS 1974. The function of the ISPS Code is to minimize the occurrence of terrorism, piracy, cargo theft, stowaways, drug smuggling, money laundering, and other related issues. Due to the numerous incidents, particularly in Indonesia, this study reviews the security risk of the XYZ Port Facility based on the ISPS Code. These research objectives are to determine the security risk rating of the XYZ Port facility and to ascertain whether risk mitigation measures are necessary for the security facilities of XYZ Port. The method used in this research involves surveys and direct observations based on field data. The risk assessment in this study consists of three evaluations: threat, vulnerability, and impact assessment. Based on this research it can be identified that the security risk assessment of XYZ port facilities across 9 aspects revealed that 7 out of the 9 aspects have a risk rating of "Document (D)," while the remaining 2 aspects have a risk rating of "Consider (C)”. Overall, it can be concluded that the security level of XYZ's port facilities is good.